Carta de James E. Watson a Roberto H. Todd - Todd, Roberto H.; Watson, James E. (My University, 1912)
Carta relacionada a dar gracias por las felicitación de Navidad.
Keywords: Watson, James E.--Correspondence.; Watson, James --Correspondencia.; Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.